Effectiveness of Shopee Live Streaming at Night on Purchasing Decisions (Case Study of CV Avero Indonesia) - Iryanti, Endang; Wigunastika, Tiara (PT FORMOSA CENDEKIA GLOBAL, 2024)
The development of technology and the internet has changed the way consumers interact with brands. Live streaming, especially via Shopee, has become an effective strategy in the digital era. This research analyzes the application of live streaming at night as an effort to influence purchasing decisions for Avero products. The research method uses descriptive qualitative with a SWOT matrix. Avero live streaming is powerful in live interactions, product presentations, and reading live comments. Disadvantages include connection disruptions and competing evening activities. Opportunities include special evening promotions and free delivery vouchers. Threats involve monotonous content and the emergence of new competitors. SO, WO, ST, and WT strategies are recommended to optimize Avero's live-streaming marketing on Shopee. The conclusion emphasizes adapting to competitors' strategies for greater live-streaming effectiveness. This research is expected to guide Shopee Live users in formulating more efficient marketing strategies.